School choice and information - Gómez, Daniel; Chumacero, Rómulo A.; Paredes, Ricardo D. (Estudios de Economía, 2012)
One of the pillars of the educational voucher system is that competition between schools to attract students would improve the quality of the education provided. Surveys in Chile have suggested that parents are not aware of the performance of their children’s schools. In this paper, we assess the effect of public information of school quality on the school choice by parents. We use a data set which includes measurements of the distance between homes and schools, and the performance of the school measured by a standardized tests and the school fee for two distinct periods (1996 and 2003). Whereas in 1996, information regarding school performance was scarce, it was widespread in 2003. We conclude that regardless of these considerations, school performance is an important determinant of school choice. Thus, parents appear to act "as if" they knew it when choosing a school. Nevertheless, making public the information regarding the performance of the schools has made it a more important factor in choosing a school.